The effects of heavy metal ions, phthalates and ochratoxin A on oxidation of carcinogenic aristolochic acid I causing Balkan endemic nephropathy - Barta, Frantisek; Levova, Katerina; Hodek, Petr; Schmeiser, Heinz H; Arlt, Volker M; Stiborova, Marie (Neuro endocrinology letters, 2015)
OBJECTIVES: Balkan endemic nephropathy (BEN) is a chronic progressive fibrosis associated with upper urothelial carcinoma (UUC). Aetiology of BEN is still not fully explained. Although carcinogenic aristolochic acid I (AAI) was proven as the major cause of BEN/UUC, this nephropathy is considered to be multifactorial. Hence, we investigated whether other factors considered as potential causes of BEN [a mycotoxin ochratoxin A (OTA), Cd, Pb, Se and As ions and organic compounds (i.e. phthalates) released from lignite deposits in BEN areas] can influence detoxication of AAI, whose concentrations are crucial for BEN development. METHODS: Oxidation of AAI to 8-hydroxyaristolochic acid I (AAIa) in the presence of Cd, Pb, Se, As ions, dibutylphthalate (DBP), butylbenzylphthalate (BBP), bis(2-ethylhexyl)phthalate (DEHP) and OTA by rat liver microsomes was determined by HPLC. RESULTS: Only OTA, cadmium and selenium ions, and BBP inhibited AAI oxidation by rat liver microsomes. These compounds also inhibited activities of CYP1A1 and/or CYP2C6/11 catalysing AAI demethylation in rat livers. Therefore, these CYP inhibitions can be responsible for a decrease in AAIa formation. When the combined effects of these compounds were investigated, the most efficient inhibition was caused by OTA combined with BBP and selenium ions. CONCLUSION: The results show low effects of BBP, cadmium and selenium ions, and/or their combinations on AAI detoxication. No effects were produced by the other metal ions (Pb, As) and phthalates DBP and DEHP. This finding suggests that they do not influence AAI-mediated BEN development. In contrast, OTA might influence this process, by inhibition of AAI detoxication.
Keywords: Metals, Heavy; kadmium; těžké kovy; Selenium; Aristolochic Acids; Lead; krysa rodu Rattus; Oxidation-Reduction; Chromatography, High Pressure Liquid; ochratoxiny; Microsomes, Liver; kyseliny aristolochové; ionty; Phthalic Acids; Carcinogens; balkánská nefropatie; olovo; selen; Ochratoxins; vysokoúčinná kapalinová chromatografie; jaterní mikrozomy; zvířata; kyseliny ftalové; arsen; oxidace-redukce; Rats; Ions; Animals; Balkan Nephropathy; karcinogeny; Arsenic; Cadmium